Polyphenol Extract of Moringa Oleifera Leaves Alleviates Colonic Inflammation in Dextran Sulfate Sodium-Treated Mice. (25th November 2020) - Zhang, Yunjuan; Peng, Lei; Li, Wenyun; Dai, Tianyi; Nie, Long; Xie, Jing; Ai, Yu; Li, Lingfei; Tian, Yang; Sheng, Jun
Abstract : Moringa oleifera Lam. is an essential herb used for the treatment of inflammation, diabetes, high blood pressure, and other diseases. In this study, phenolic extracts of M. oleifera leaves were obtained and analyzed. The results showed that the main identifiable phenols were astragalin, chlorogenic acid, isoquercitrin, kaempferitrin, luteolin, quercetin, and rutin. The effects of M. oleifera polyphenol extract (MOPE) on experimental colitis induced by 3% dextran sulfate sodium (DSS) were investigated. The results showed that oral administration of MOPE significantly alleviated the symptoms of DSS-induced colitis. MOPE significantly reduced weight loss, the disease activity index, colon shortening, and mucosal damage. In addition, MOPE attenuated the infiltration of CD3 + T cells, CD177 + neutrophils, and F4/80 + macrophages and significantly inhibited the secretion of IL-6 and TNF- α . After the MOPE administration, the expression of proteins associated with the NF- κ B signaling pathway changed. Specifically, compared with that of the DSS group, the protein expression of NF- κ B p65 and p-I κ B α was downregulated, and the expression of I κ B α was upregulated. This study revealed the anti-inflammatory effects and mechanisms of MOPE in the colon, indicating its potential use in preventing inflammation-driven diseases.